2021
DOI: 10.1021/acs.analchem.1c00337
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Carbon Nanoparticles Capable of Long-Term Tracking Lipid Droplet for Real-Time Monitoring of Lipid Catabolism and Pharmacodynamic Evaluation of Lipid-Lowering Drugs

Abstract: Lipid droplets (LDs) are intracellular lipid-rich organelles, which not only serve as neutral lipid reservoirs but also involve in many physiological processes and are associated with a variety of metabolic diseases and cancers. Long-term tracking of the state and behavior of LDs is of great significance but challenging. The difficulty is largely due to the lack of low cytotoxicity, high photobleaching resistance, and long intracellular retention probes that are capable of long-term tracking LDs. Herein, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…41 The fluorescence properties of the O-CDs were measured in various proportions of glycerol-water mixtures which could generate different viscosities. 18 The results showed that the fluorescence intensity of the O-CDs increased more than 8.3 times in the mixture solution containing 80% glycerol (Fig. 5h).…”
Section: The Binding Mechanism Of Cu 2+ With the O-cdsmentioning
confidence: 86%
See 1 more Smart Citation
“…41 The fluorescence properties of the O-CDs were measured in various proportions of glycerol-water mixtures which could generate different viscosities. 18 The results showed that the fluorescence intensity of the O-CDs increased more than 8.3 times in the mixture solution containing 80% glycerol (Fig. 5h).…”
Section: The Binding Mechanism Of Cu 2+ With the O-cdsmentioning
confidence: 86%
“…Since the concept of "carbon dots (CDs)" was proposed in 2004, 11 CDs have shown promising application prospects 12 because of their fluorescence characteristics, 13,14 good biocompatibility, 15 modifiable properties, 16 and quantum yield adjustability. 17 For instance, CDs have comprehensive applications in biological imaging, 18 cancer therapy, 19,20 drug delivery, 21 and electrochemical luminescence. 22 In particular, they can be easily and inexpensively synthesized by top-down or bottom-up chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Despise these advances, many organic probes still suffer several drawbacks, including poor water solubility, nonspecific staining, and shorter time of intracellular retention [72]. In this sense, the development of nanostructures to act as imaging or delivery imaging agents to LDs may help to overcome these problems.…”
Section: Imaging Strategiesmentioning
confidence: 99%
“…These nanoparticles show excellent properties, such as water solubility, biocompatibility, and photostability. Liu et al [72] developed a one-pot synthesis of CNPs based on o-phenylenediemine (oPD) and carbon dots (CDs). To ensure staining specificity, co-localization studies were performed using Nile Red as the control.…”
Section: Imaging Strategiesmentioning
confidence: 99%
“…In order to visualize LDs and investigate their multiple capabilities, fluorescence imaging techniques (such as wide field, confocal, and two-photon) are generally employed. Therefore, a lot of LDs fluorescent probes have been reported for these fluorescence imaging techniques. Unfortunately, the resolutions of these imaging techniques are intrinsically limited to be about 250 nm (half value of the wavelength) due to light diffraction. Thus, these imaging techniques are not competent for visualizing the small nascent LDs.…”
mentioning
confidence: 99%